PENGARUH OWNERSHIP STRUCTURE TERHADAP ECONOMIC VALUE ADDED MELALUI VOLUNTARY DISCLOSURE IN CORPORATE GOVERNANCE SEBAGAI VARIABEL MEDIASI (STUDI KASUS PADA PERUSAHAAN PERTAMBANGAN DI INDONESIA) - Stifanny Christin Okhotan; Saarce Elsye Hatane (Business Accounting Review, 2018)
This study aimed to examine the direct and significant influence between ownership structure to economic value added as well as to know the indirect influence between the ownership structure on economic value added through voluntary disclosure in corporate governance as the mediation variable. The samples used in this research were 39 mining companies listed in Indonesia Stock Exchange starting from 2011-2016. Data processed by using WarpPLS software version 5.0.The result of the research found the positive affect of ownership structure on voluntary disclosure in corporate governance, positive influence of ownership structure to economic value added, positive influence of voluntary disclosure in corporate governance to economic value added, and the voluntary disclosure in corporate governance successfully mediated the influence of the ownership structure on economic value added.